Targeting Th9 cells in autoimmune diseases: a narrative review - Wang-Dong Xu; You-Yue Chen; Yun-Wei Li; Jing Yang; An-Fang Huang (Frontiers in Immunology)
T helper 9 (Th9) cells are a newly identified subset of effector T cells, characterized by their production of IL-9, a hallmark cytokine. Transcription factors such as PU.1 and IRF4 bind to the IL9 gene promoter and transactivate its expression. IL-9 and its associated transcription factors regulate various aspects of Th9 cell biology, including proliferation, apoptosis, differentiation, and interactions with other immune cells through downstream signaling pathways. In recent years, the involvement of Th9 cells in autoimmune diseases has been widely investigated. Multiple studies have reported the aberrant expression of IL-9, PU.1, and IRF4 in these inflammatory conditions, and functional analyses have demonstrated their significant roles in disease development. In this review, we comprehensively summarize the relationship among Th9-related cytokines, transcription factors, and 14 autoimmune diseases based on both in vivo and in vitro evidence. We further discuss the regulatory effects of intracellular and extracellular signaling pathways on Th9 cell functions. This compilation of findings may facilitate future research and the development of clinical strategies targeting Th9 cells in autoimmune diseases.